2004
DOI: 10.1002/yea.1126
|View full text |Cite
|
Sign up to set email alerts
|

The trehalose pathway and intracellular glucose phosphates as modulators of potassium transport and general cation homeostasis in yeast

Abstract: Trk, encoded by the partially redundant genes TRK1 and TRK2, is the major potassium transporter of Saccharomyces cerevisiae. This system is specific for potassium and rubidium but, by reducing the electrical membrane potential of the plasma membrane, Trk decreases the uptake of toxic cations such as lithium, calcium, aminoglycosides and polyamines, which are transported by other systems. Gain-and loss-of-function studies indicate that TPS1, a gene encoding trehalose-6-phosphate synthase and known to modulate g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…role in salt and pH tolerance in yeast through regulating the trafficking of the potassium transporters Trk1p and Trk2p (47,52). CKII is involved in multiple processes, including the cell cycle, cell polarization, and transcription regulation (53).…”
Section: S 251amentioning
confidence: 99%
“…role in salt and pH tolerance in yeast through regulating the trafficking of the potassium transporters Trk1p and Trk2p (47,52). CKII is involved in multiple processes, including the cell cycle, cell polarization, and transcription regulation (53).…”
Section: S 251amentioning
confidence: 99%
“…However, the downstream signaling targets that modulate vacuolar Ca 2ϩ uptake remain to be identified. In a recent study, Mulet and coworkers (30) reported that trehalose 6-phosphate synthase (TPS)1 activity alters the ion transport characteristics of the K ϩ channels TRK1 and TRK2 through the modulation of cellular Glc phosphate levels. They also noted that like TPS1, PGM and hexokinase 2 are also capable of altering the levels of Glc phosphates and that elevated Glc phosphate levels activate TRK by way of the calcineurin pathway (30).…”
Section: LImentioning
confidence: 99%
“…Paromomycin and rapamycin were added at the indicated concentration from a concentrated stock to autoclaved yeast extract/peptone/dextrose with 2% agar prior to gelation. Spot tests of yeast growth were performed as described previously (23), but plates were incubated at a restrictive temperature (37°C) for the thermosensitive allele of TOR2. Immunoprecipitation assays were performed as described previously (24).…”
Section: Methodsmentioning
confidence: 99%